Tattoo-associated panuveitis: A 10-year follow-up. Issue 1 (July 2019) - Tiew, Stephenie
Introduction: There has been an increasing number of tattoo-related uveitis without evidence of systemic sarcoidosis. This finding may indicate a possible association of tattoos with uveitis. Case description: This report is a 10-year follow-up of a single case of tattoo-related uveitis with no proven systemic sarcoidosis. Conclusion: Literature review suggests possible pathogenesis and the patient's management is discussed. This case highlights the importance of a good systemic history and physical examination, especially with regard to tattoos.